SPE Latin American and Caribbean Petroleum Engineering Conference 2001
DOI: 10.2118/69581-ms
|View full text |Cite
|
Sign up to set email alerts
|

First Massive Hydraulic Fracturing Treatment in Argentina

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractIn the last two decades, it was usual practice in the oil industry to carry out massive hydraulic fracturing works to stimulate wells with great-heighten layers of interest and/or low permeability sands.Argentina has had no opportunity so far to make a stimulation work of this type, mainly because of the absence of a layer meeting the principal characteristics needed to carry out a job of this size, considering the lack of equipment required by a service comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Since its introduction in the late 1940s, hydraulic fracturing has been widely used in North America to achieve higher recovery from low permeability reservoirs and/or to bypass the formation damage around the wellbore (Economides, et al, 2002). In addition, successful applications of this technique have been reported in other locations including North Sea (Vos, et al, 2009), South America (Antoci and Anaya, 2001), Asia (Shaoul, et al, 2007) and Middle East (Al-Zarouni and Ghedan, 2012) and (Mirzaei-Paiaman, 2013). Generally, many steps of analysis are performed prior to any hydraulic fracturing job to ensure its effectiveness.…”
Section: Introductionmentioning
confidence: 98%
“…Since its introduction in the late 1940s, hydraulic fracturing has been widely used in North America to achieve higher recovery from low permeability reservoirs and/or to bypass the formation damage around the wellbore (Economides, et al, 2002). In addition, successful applications of this technique have been reported in other locations including North Sea (Vos, et al, 2009), South America (Antoci and Anaya, 2001), Asia (Shaoul, et al, 2007) and Middle East (Al-Zarouni and Ghedan, 2012) and (Mirzaei-Paiaman, 2013). Generally, many steps of analysis are performed prior to any hydraulic fracturing job to ensure its effectiveness.…”
Section: Introductionmentioning
confidence: 98%
“…Sea (Vos, et al, 2009), South America (Antoci & Anaya, 2001), Asia (Shaoul, et al, 2007) and Middle East (Al-Zarouni & Ghedan, 2012) have been reported.…”
mentioning
confidence: 99%